2006
DOI: 10.1111/j.1439-0523.2006.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and identification of markers associated with yield traits in mulberry using ISSR markers

Abstract: Mulberry (Morus indica L.) is an important tree crop being exploited for feeding the silk-producing insect Bombyx mori L. In order to identify parents suitable for breeding to raise high-yielding varieties for the non-traditional areas of Kerala, India and also to identify markers associated with leaf yield attributing traits, the present study was undertaken with 44 mulberry genotypes. Variability on morphobiometric traits and molecular markers, generated with 12 selected ISSR primers, was estimated. Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 24 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Genetic linkage maps have been developed for chickpea in different research works (Jain, Chattopadhyay, 2010;Gaur et al, 2011), and QTLs controlling different traits such as double podding and other morphological traits (Gaur et al, 2011), as well as drought tolerance (Jain, Chattopadhyay, 2010) have been identified. Identification of markers associated with important traits in a group of genotypes through association mapping offers an alternative means, as has been used in several plants species (Vijayan et al, 2005;Roy et al, 2006;Darvishzadeh et al, 2008). Roy et al (2006) by using the phenotypic data of 55 elite wheat genotypes for 14 different agronomic traits and molecular data produced by 20 simple sequence repeat (SSR), 2 selectively amplified microsatellite polymorphic loci (SAMPL) and 8 amplified fragment length polymorphism (AFLP) primer combinations (in total 519 deoxyribonucleic acid (DNA)-based molecular markers), reported some molecular markers associated with traits via simple or multiple linear regression analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic linkage maps have been developed for chickpea in different research works (Jain, Chattopadhyay, 2010;Gaur et al, 2011), and QTLs controlling different traits such as double podding and other morphological traits (Gaur et al, 2011), as well as drought tolerance (Jain, Chattopadhyay, 2010) have been identified. Identification of markers associated with important traits in a group of genotypes through association mapping offers an alternative means, as has been used in several plants species (Vijayan et al, 2005;Roy et al, 2006;Darvishzadeh et al, 2008). Roy et al (2006) by using the phenotypic data of 55 elite wheat genotypes for 14 different agronomic traits and molecular data produced by 20 simple sequence repeat (SSR), 2 selectively amplified microsatellite polymorphic loci (SAMPL) and 8 amplified fragment length polymorphism (AFLP) primer combinations (in total 519 deoxyribonucleic acid (DNA)-based molecular markers), reported some molecular markers associated with traits via simple or multiple linear regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Darvishzadeh et al (2008) by using multiple linear regression analysis identified putative AFLP markers associated with partial resistance to phoma black stem in 60 sunflower mutant lines. Vijayan et al (2005) genotyped 44 mulberry genotypes with inter-simple sequence repeat (ISSR) markers and identified putative markers associated with leaf yield attributing traits. The potential of association mapping to identify and characterize loci/genes associated with different complex traits is highly affected by admixture of populations (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, the identification of molecular markers associated with trait of interest through multiple regression analysis, involving the use of diverse germplasm collections have so far been adopted in many crop species (Maureira-Butler et al, 2007;Dholakia et al, 2008;Ruan et al, 2009). These include RAPD markers associated with various polygenic traits in Asian rice (Virk et al, 1996) and protein content in wheat (Dholakia et al, 2001), SCAR markers associated with birch fiber length trait (Wang et al, 2008), ISSR markers associated with various yield traits (Vijayan et al, 2006) and protein content (Kar et al, 2008) in mulberry, and microsatellite markers associated with seed size in soybean (Hoeck et al, 2003) and mite resistance in coconut (Shalini et al, 2007). The present study involves an evaluation of genetic diversity and use of multiple regression analysis to validate the molecular markers associated with sheath blight resistance in rice.…”
Section: Introductionmentioning
confidence: 99%
“…Random amplified polymorphic DNA (RAPD)-linked markers associated with production yield and its components in Miscanthus sinensis, 9) fruit sugar concentration in tomato, 10) S-glycoprotein in Brassica campestris, 11) and inter-simple-sequence repeat (ISSR) markers linked to yield traits in mulberry, 12) horticultural traits for watermelon, 13) seasonal flowering locus in Fragaria have been successfully identified. Also the prediction models for quantity traits have been effectively applied in the crop productions, such as prediction models for mite resistance with molecular markers in coconut, 14) genetic and environmental effects on chemical composition related to sensory traits in common beans, 15) and prediction of yield component performances in hybrid rice using molecular markers technology.…”
mentioning
confidence: 99%